Stalled Hox promoters as chromosomal boundaries. - Chopra, V.S.; Cande, J.; Hong, J.W.; Levine, M. (Genes & Development, 2009)
Many developmental control genes contain stalled RNA Polymerase II (Pol II) in the early Drosophila embryo, including four of the eight Hox genes. Here, we present evidence that the stalled Hox promoters possess an intrinsic insulator activity. The enhancer-blocking activities of these promoters are dependent on general transcription factors that inhibit Pol II elongation, including components of the DSIF and NELF complexes. The activities of conventional insulators are also impaired in embryos containing reduced levels of DSIF and NELF. Thus, promoter-proximal stalling factors might help promote insulator-promoter interactions. We propose that stalled promoters help organize gene complexes within chromosomal loop domains.